Ef24, a schistosomicidal curcumin analog : insights from its synthesis and phenotypic, biochemical and cytotoxic activities - Badoco, Fernanda Rafacho (2022)
Agradecimentos: The authors thank the Electron Microscopy Laboratory in Ribeirão Preto, University of São Paulo, Brazil, for their help with the TEM. The authors also thank Ana Júlia Afonso, Julia Medeiros Souza, Neusa Araújo, Heloiza D. Nicolella and Olinda Mara Brigatto for their technical support, CBMM for supplying niobium pentachloride samples and James H. McKerrow of the Center for Discovery and Innovation in Parasitic Diseases, Skaggs School of Pharmacy and Pharmaceutical Sciences, University of California San Diego for his generous advice. S. mansoni-infected hamsters (for the maintenance and production of the NMRI isolate of S. mansoni) were partly provided by the National Institute of Allergy and Infectious Diseases (NIAID) Schistosomiasis Resource Center of the Biomedical Research Institute (Rockville, MD, USA) through the National Institutes of Health (NIH)-NIAID Contract HHSN272201700014I for distribution through BEI Resources. The authors thank Espaço da Escrita – Pró-Reitoria de Pesquisa - UNICAMP - for the language services provided. This study was supported by the National Council for Scientific and Technological Development, Brazil–CNPq (Fellowship: 303946/2018-0), Coordination for the Improvement of Higher Education Personnel, Brazil-CAPES (Finance Code 001) and State of São Paulo Research Foundation -FAPESP (Grant numbers: 2016/24456-1, 2016/18045-9, 2017/24856-2 and 2018/50011-2 and Fellowships: 2014/02018-7, 2015/01394-8). C.R.C. acknowledges R21AI126296 from the NIH and OPP1171488 from the Bill and Melinda Gates Foundation